The rate of substrate cycling between fructose 6-phosphate and fructose 1,6-bisphosphate in skeletal muscle. - Challiss, R A (1984)
Substrate cycling of fructose 6-phosphate through reactions catalysed by 6-phosphofructokinase and fructose-1,6-bisphosphatase was measured in skeletal muscles of the rat in vitro. The rate of this cycle was calculated from the steady-state values of the 3H/14C ratio in hexose monophosphates and fructose 1,6-bisphosphate after the metabolism of either [5-3H,6-14C]glucose or [3-3H,2-14C] glucose. Two techniques for the separation of hexose phosphates were studied; t.l.c. chromatography on poly(ethyleneimine)-cellulose sheets or ion-exchange chromatography coupled with enzymic conversion. These two methods gave almost identical results, suggesting that either technique could be used for determination of rates of fructose 6-phosphate/fructose 1,6-bisphosphate cycling. It was found that more than 50% of the 3H was retained in the fructose 1,6-bisphosphate; it is therefore probable that previous measurement of cycling rates, which have assumed complete loss of 3H, have underestimated the rate of this cycle. The effects of insulin, adrenaline and adrenergic agonists and antagonists on rates of fructose 6-phosphate/fructose 1,6-bisphosphate cycling were investigated. In the presence of insulin, adrenaline (1 microM) increased the cycling rate by about 10-fold in epitrochlearis muscle in vitro; the maximum rate under these conditions was about 2.5 mumol/h per g of tissue. The concentration of adrenaline that increased the cycling rate by 50% was about 50 nM. This effect of adrenaline appears to be mediated by the beta-adrenergic receptor, since the rate was increased by beta-adrenergic agonists and blocked by beta-adrenergic antagonists. From the knowledge of the precise rate of this cycle, the possible physiological importance of cycling is discussed.